Eksplorasi Minat Warga Korea Selatan terhadap Batik Indonesia - Putri Rizki Utami; Muhammad Aqshel Revinzky (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Globalization is a world development phenomenon where everything can be achieved instantly and makes things easier for humans in everything, whether in the use of technology or information obtained in gaining knowledge with just one click. However, in the 20th century, the development of this phenomenon became increasingly rapid and global. This is due to advances in technology and the ease with which information can be obtained via the internet which is used by almost all people in the world. Indonesian people take advantage of this phenomenon in distributing and introducing traditional Indonesian culture to foreign countries, especially South Korea. One of the Indonesian cultural products that can be exported is Indonesian batik which has been recognized by UNESCO as a world cultural heritage.This research aims to analyze the impact of globalization on Indonesian batik export opportunities to South Korea. This research uses a qualitative method with a phenomenological approach. The object of research is Indonesian batik which has successfully attracted the attention of the people in South Korea. This data was collected through interviews with local South Korean residents, observations, and literature studies.The research results show that globalization has had a positive impact on batik export opportunities in Indonesia. This can be seen from the increasing consumption of Indonesian products in South Korea and the interest of the South Korean people in learning Indonesian and its culture. Apart from that, through this research, other factors were found that influence the export opportunities of Indonesian batik to South Korea, including the quality of Indonesian batik, Indonesian and South Korean government policies, as well as the promotion of Indonesian batik in South Korea. Therefore, Indonesian business people need to take advantage of this opportunity to increase Indonesian batik exports to South Korea.